2017
DOI: 10.1016/j.jval.2016.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Patient Versus Physician Valuation of Durable Survival Gains: Implications for Value Framework Assessments

Abstract: Patients place a high value on therapies that provide a chance of durable or "tail-of-the-curve" survival, whereas physicians do not. Value frameworks should incorporate measures of tail-of-the-curve survival gains into their methodologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 31 publications
0
57
1
Order By: Relevance
“…Technologies that provide an opportunity for a cure would thus be more valuable to many patients, and a payer, acting as their agent, would be willing to pay more on their behalf. Empirical work relying on discrete choice experiments provides support for this element and demonstrates how to value it [31,33].…”
Section: Value Of Hopementioning
confidence: 99%
“…Technologies that provide an opportunity for a cure would thus be more valuable to many patients, and a payer, acting as their agent, would be willing to pay more on their behalf. Empirical work relying on discrete choice experiments provides support for this element and demonstrates how to value it [31,33].…”
Section: Value Of Hopementioning
confidence: 99%
“…A minority of oncologists, on the other hand, would select the therapy with a chance of durable survival for patients with melanoma (29.7%) or lung cancer (40.8%). 20 Although the hypothetical treatment profiles evaluated in these studies and in our study differed, the results reveal consistently divergent priorities between patients and physicians.…”
Section: Discussionmentioning
confidence: 53%
“…12 This phenomenon has been termed the value of hope. 12 Several studies have explored the value that patients, providers, or both place on aspects of benefits and burdens of treatment, including progression-free survival (PFS), landmark overall survival (OS), or toxicities in lung cancer, 13–22 melanoma, 12 , 20 , 23 , 24 and renal cell carcinoma. 25–28 However, no study to date has been designed to elicit how patients and their physicians value a set of attributes with the unique profile of immuno-oncologic treatments, including how patients and physicians trade off increases in mean or median survival versus an increased chance of remission or durable survival or avoiding toxicities associated with cytotoxic chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In one-way sensitivity analysis (Figure 3), we found that the utility values of PFS are the most significant parameter that could change the ICER value. Generally, utility is influenced by the social and cultural values of the stakeholders, and therefore it might differ across countries 3638. However, in the present study, the utilities were not directly obtained from the LUX-lung 6 trial or a Chinese population.…”
Section: Discussionmentioning
confidence: 95%
“…We assumed patients from both treatment groups received docetaxel after disease progression, which may not always mimic the treatment in the real world because patients might switch to subsequent therapy upon the further progressions, for example the use of platinum-based combination chemotherapy is also possible after the failure of EGFR inhibitors. Fourth, our value frameworks rely on efficacy measures based on improvements in survival rate of median patients, and hence did not take into account of the improvements in “tail of the curve survival”, which may impact the current treatment decisions 38. Finally, we have identified for healthcare policymakers in China whether afatinib strategy is of the best value for money.…”
Section: Discussionmentioning
confidence: 99%